2009
DOI: 10.1074/mcp.m900127-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Protein Pentosidine and Carboxymethyllysine, Biomarkers for Age-related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) causes severe vision loss in the elderly; early identification of AMD risk could help slow or prevent disease progression. Toward the discovery of AMD biomarkers, we quantified plasma protein Nε-carboxymethyllysine (CML) and pentosidine from 58 AMD and 32 control donors. CML and pentosidine are advanced glycation end products that are abundant in Bruch membrane, the extracellular matrix separating the retinal pigment epithelium from the blood-bearing choriocapillaris. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 44 publications
2
61
1
Order By: Relevance
“…Crabb et al demonstrated that carboxyethyl pyrrole (CEP) protein adducts, the oxidative protein modifi cations generated uniquely from the docosahexaenoate-containing lipids such as DHA and adrenic acid ( 51 ), are more abundant in ocular tissues from AMD retina than from normal retina ( 52 ). CEP biomarkers have been shown to enhance the AMD predictive accuracy of genomic AMD biomarkers ( 53,54 ). The increase of CEP protein adducts in AMD retinas indicates that increased oxidation of DHA and adrenic acid that likely occurs in AMD eyes may lead to a reduction in DHA and adrenic acid, which is consistent with our study results.…”
Section: Separation Of Vlc-pufas From Retina and Rpe/choroidsupporting
confidence: 91%
“…Crabb et al demonstrated that carboxyethyl pyrrole (CEP) protein adducts, the oxidative protein modifi cations generated uniquely from the docosahexaenoate-containing lipids such as DHA and adrenic acid ( 51 ), are more abundant in ocular tissues from AMD retina than from normal retina ( 52 ). CEP biomarkers have been shown to enhance the AMD predictive accuracy of genomic AMD biomarkers ( 53,54 ). The increase of CEP protein adducts in AMD retinas indicates that increased oxidation of DHA and adrenic acid that likely occurs in AMD eyes may lead to a reduction in DHA and adrenic acid, which is consistent with our study results.…”
Section: Separation Of Vlc-pufas From Retina and Rpe/choroidsupporting
confidence: 91%
“…Accumulation of AGEs is diagnostic of many age-related diseases, including AMD, and is a reporter of chronic hyperglycemia and its downstream glycoxidative and other cytotoxic stresses (13,(30)(31)(32). Plasma levels of the AGEs, including glucosepane, Ne(1-carboxyethyl)-lysine (CEL), and 3-deoxyglucosone-derived hydroimidazolone (3DG-H), were all higher in these HG nondiabetic mice ( Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Proteomic analysis of Bruch's membrane from human eyes with AMD revealed the presence of oxidized compounds. 17 The Eye Disease Case Control Study found an association between reduced prevalence of AMD and high dietary intake of antioxidants. 18 The placebo-controlled, double-masked multicenter clinical Age-Related Eye Disease Study provided strong support for the relationship between AMD and oxidants by finding reduced progression to advanced AMD and vision loss in subjects who took certain antioxidants and zinc supplements.…”
mentioning
confidence: 99%